2021
DOI: 10.3390/ma14092340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Scanning-Aid Materials on the Accuracy and Time Efficiency of Intraoral Scanners for Full-Arch Digital Scanning: An In Vitro Study

Abstract: This study was performed to verify the influence of scanning-aid materials on the accuracy and time efficiency of full-arch scanning with intraoral scanners. The full-arch reference model was constructed by a 3D printer and scanned with a model scanner to obtain the reference dataset. Four experimental groups (application of ScanCure (SC-80, ODS Co, Incheon, Korea), IP Scan Spray (IP-Division, Haimhausen, Germany) and Vita Powder Scan Spray (Vita Zahnfabrik, Stuttgart, Germany), and no treatment) were designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
(27 reference statements)
0
24
0
Order By: Relevance
“…The less accurate reproduction of the attachments may be present in models with asymmetries between the right and left sides of the arch. This inaccuracy could be because the intraoral scanner constructs the image using mirror reproduction [ 33 ].…”
Section: Discussion and Results Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…The less accurate reproduction of the attachments may be present in models with asymmetries between the right and left sides of the arch. This inaccuracy could be because the intraoral scanner constructs the image using mirror reproduction [ 33 ].…”
Section: Discussion and Results Interpretationmentioning
confidence: 99%
“…The authors decided not to coat the models with powders or liquids because scanning-aid materials can be more effective on metallic surfaces than resin-like materials [ 33 ]. In addition, the manufacturer does not recommend it.…”
Section: Methodsmentioning
confidence: 99%
“…They found that the application of titania powder before Omnicam scanning improves the vertical fit of crowns and decreases the 3D luting space (i.e., the application of powder affected the edge difference of the crowns). Hyun‐Su Oh et al 112 analyzed the influence of scanning‐aid materials in a set of four experimental groups (three different types of scanning‐aid materials groups and one no‐application group) on two intraoral scanners and found that the application of powder can reduce scanning time and more efficiently obtain full‐arch scanned images. However, if the powder is applied unevenly, it can result in inaccurate scanning of certain areas, increase scanning time, and cause patient discomfort 113 .…”
Section: Factors Influencing the Performance Of 3d Imaging Devicesmentioning
confidence: 99%
“…For instance, not only the matching algorithms of software, but also the sensor quality of the intraoral scanner must be improved [ 17 ]. Scanning strategies such as scanning path, environment control, and application of scanning-aid agents are used to obtain accurate scanned images [ 10 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to reduce the reflective properties of the metallic surface and increase the accuracy in the case of a long span, surface treatments, such as the application of scanning-aid agents, are frequently suggested. A previous study reported that when a resin-based full-arch model was scanned with the application of scanning-aid materials, the precision of root mean square (RMS) values was improved [ 18 ].…”
Section: Introductionmentioning
confidence: 99%